Phenobarbital as an adjunctive agent for sedation in pediatric intensive care unit patients: A single-center, retrospective study from Colorado - Kelli Jo Welter; Mackenzie N. DeVine; Sharon E. Gordon; Gina Demasellis (Wolters Kluwer Medknow Publications, 2024)
Background: Pediatric patients require pharmacological management of pain and agitation associated with mechanical ventilation. Pain and agitation may be refractory to opioids and alpha-2 agonists, prompting the use of adjunctive analgesics and sedatives with alternative mechanisms. The purpose of this study was to describe the use of phenobarbital as an adjunctive agent for refractory agitation in critically ill, mechanically ventilated pediatric patients. Subjects and Methods: This was a single-center, retrospective chart review at a pediatric intensive care unit (PICU) at a pediatric academic medical center in America between 2016 and 2021. Children aged 2 months to 18 years old were admitted to the PICU were mechanically ventilated and received phenobarbital for adjunct sedation. Sixty-three patients had phenobarbital dosing data evaluated, and the 38 patients who were not receiving continuous neuromuscular blockade were included in the primary and secondary outcome analysis of time within the goal sedation score. Descriptive statistics was used to assess baseline characteristics and the primary outcome. Wilcoxon signed-rank tests were used to evaluate secondary outcomes. Results: Patients spent significantly more time within the goal sedation score range after phenobarbital compared to before phenobarbital. The median number of rescue sedative boluses, morphine equivalents (MEs), and benzodiazepine equivalents (BZDE) significantly decreased 2 days after the first phenobarbital dose compared to the 2 days before the first phenobarbital dose. Conclusions: The use of phenobarbital as an adjunct sedative was associated with a statistically significant increase in time spent in the goal sedation score range and decrease in ME, BZDE, and concomitant sedative boluses.